Neutralization of acidic drainage by Cryptococcus sp. T1 immobilized in alginate beads. Issue 11 (2nd November 2017) - Okai, Masahiko; Suwa, Chisato; Nagaoka, Shintaro; Obara, Nobuo; Mitsuya, Daisuke; Kurihara, Ayako; Ishida, Masami; Urano, Naoto
Abstract: We isolated Cryptococcus sp. T1 from Lake Tazawa's acidic water in Japan. Cryptococcus sp. T1 neutralized an acidic casamino acid solution (pH 3.0) and released ammonia from the casamino acids to aid the neutralization. The neutralization volume was estimated to be approximately 0.4 mL/h. The casamino acids' amino acids decreased (1.24→0.15 mM); ammonia increased (0.22→0.99 mM). We neutralized acidic drainage water (1 L) from a Tamagawa River neutralization plant, which was run through the column with the T1-immobilized alginate beads at a flow rate of 0.5 mL/min, and observed that the viscosity, particle size and amounts of the alginate beads affected the acidic drainage neutralization with an increase of the pH value from 5.26 to 6.61 in the last fraction. An increase in the Al concentration decreased Cryptococcus sp. T1's neutralization ability. After 48 h, the pH of acidic water with 50 mg/L Al was apparently lower than that without Al. Almost no pH increase was observed at 75 mg/L. Abstract : : A bioreactor with Cryptococcus sp. T1-immobilized in alginate beads neutralized an acidic casamino acid solution and acidic drainage.